Angle-dependent sputter yield measurements of keV D ions on W and Fe and comparison with SDTrimSP and SDTrimSP-3D. (January 2019) - Arredondo, R.; Oberkofler, M.; Schwarz-Selinger, T.; von Toussaint, U.; Burwitz, V.V.; Mutzke, A.; Vassallo, E.; Pedroni, M.
Highlights: Angle-dependent sputter yield of 2 keV D on Fe and W measured and compared to SDTrimSP. Sputtering behavior of smooth and rough W studied. First experimental benchmark of SDTrimSP-3D. Abstract: The influence of surface roughness on the sputter yield was investigated as a function of the angle of incidence. In this work, nm-smooth and rough samples with roughnesses on the µm length scale were produced by depositing thin Fe and W films on smooth and rough Si substrates via magnetron sputtering. The surface morphology of the samples was determined by atomic force microscopy. The samples were exposed to a 6 keV D3 + ion beam (2 keV/D) under various angles of incidence ranging from 0° to 75° with respect to the surface normal to fluences of the order of 10 22  D/m 2 . The layer thickness was measured by Rutherford backscattering spectrometry (RBS) before and after erosion. The resulting sputter yields were compared to simulations performed with SDTrimSP (static and dynamic) and SDTrimSP-3D (static), showing good qualitative agreement in all cases, as well as agreement with literature data at normal incidence. This constitutes the first experimental benchmark of SDTrimSP-3D. A discrepancy in the value of the sputter yield for smooth W at normal incidence was observed between the SDTrimSP simulations and the experimental values obtained in this work and found in literature. Analogous experiments were performed to study the sputter yield at normal incidence of 2 keV/D on smooth Au and 6 keV He on smooth W. These sputter yields were also compared to SDTrimSP simulations and literature, showing good agreement in all cases.